Antifungal effect and chemical study of Eysenhardtia polystachya (Fabaceae) on Phanerochaete chrysosporium and Ganoderma lucidum - Ramírez López, César Bonifacio; Pérez-Mayorga, Sonia; Ramírez Briones, Ernesto; Macias Rodríguez, Ramón; Salcedo-Pérez, Eduardo (Revista Mexicana de Ciencias Agrícolas, 2023)
Forest species are a source of timber and non-timber products. In addition to being important in obtaining botanical extracts, they contain in their tissues numerous secondary metabolites that have been recognized for their diversity and biological activity, considered as an alternative against fungi that cause rot and degradation in wood (xylophagous fungi), as well as fungi that cause diseases in agricultural crops. In this sense, it was proposed to study Eysenhardtia polystachya as a natural preservative source of wood due to its high resistance to stem rot. For this, extracts were obtained from leaf, sapwood, and heartwood with solvents of different polarities. Scrutiny and selection of the extracts with greater efficacy in Phanerochaete chrysosporium and Ganoderma lucidum were carried out; they were subjected to column chromatography. The content of phenols and flavonoids was determined. The leaf extracts showed selectivity regarding mycelial inhibition in P. chrysosporium, with greater sensitivity to the extracts than G. lucidum. The synergistic effect of the compounds present favors inhibition in P. chrysosporium. Therefore, E. polystachya presents chemical compounds that can preserve the wood and prolong its use time against attack by xylophagous fungi and generate control in phytopathogenic fungi.